2018
DOI: 10.26508/lsa.201800178
|View full text |Cite
|
Sign up to set email alerts
|

Interaction modulation through arrays of clustered methyl-arginine protein modifications

Abstract: Extensively modifiable arrays of clustered arginines in a large set of human proteins function as regulatory protein interaction platforms. Quantitative immunoprecipitation assays defined two distinct cumulative binding mechanisms operating across an array of 18 methyl-arginine motifs in SYNCRIP.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…We show that ArgMet NMR enables detection of methylation patterns in purified proteins incubated with PRMT1. Methylation by PRMTs in the human proteome occurs preferentially (but not exclusively) within glycine-arginine-rich and proline-glycine-methionine-rich regions ( Cheng et al., 2007 ; Thandapani et al., 2013 ; Woodsmith et al., 2018 ), but specific consensus sequences targeted by most of the human PRMTs remain to be identified. Our approach provides a toolbox for fast and label-free screening for PRMT selectivity in purified proteins/peptides, complementary to peptide arrays ( Kusevic et al., 2016 ) and mass spectrometry ( Uhlmann et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…We show that ArgMet NMR enables detection of methylation patterns in purified proteins incubated with PRMT1. Methylation by PRMTs in the human proteome occurs preferentially (but not exclusively) within glycine-arginine-rich and proline-glycine-methionine-rich regions ( Cheng et al., 2007 ; Thandapani et al., 2013 ; Woodsmith et al., 2018 ), but specific consensus sequences targeted by most of the human PRMTs remain to be identified. Our approach provides a toolbox for fast and label-free screening for PRMT selectivity in purified proteins/peptides, complementary to peptide arrays ( Kusevic et al., 2016 ) and mass spectrometry ( Uhlmann et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, many SARS-CoV-2 Ninteracting proteins (27 of 119, Figure 2B) contained multiple RGG/RG motifs including DEAD/DExH family of RNA helicases DDX21, DDX54, DHX30, DHX57, and heterogeneous nuclear ribonucleoproteins hnRNPA1, A3, D, DL, G (RBMX), R, U, UL1 and UL2 (Table 1). Many of these N-interacting proteins, such as G3BP1 [50], FAM98A [51], FXR1 [52], hnRNPA1 [53], hnRNPUL1 [54], SYNCRIP [55], ILF3 [56], and SERBP1 [57] are known PRMT1 substrates. N protein-interactome changed significantly by two proteins with MS023 treatment.…”
Section: The Sars-cov-2 N Interactome Defines a Complex Of Rgg/rg Proteins And Prmt1mentioning
confidence: 99%
“…hnRNP R is involved in axonal RNA transport and processing, the expression of immunity factors, and transcription and degradation process of c-fos mRNA [11, 16, 23, 49], whilst hnRNP Q, also known as SYNCRIP, is implicated in the maintenance of circadian rhythms and be involved in the regulation of mRNAs responsible for neuronal morphogenesis [10, 25, 31]. Both proteins are known to interact with the survival motor neuron (SMN) protein [1] and be involved in pre-mRNA splicing as components of the spliceosome [9, 38, 51, 56]. Recent analysis of these proteins in a cellular model has found them to be important regulators of neuronal homeostasis and indicated that their disruption could impair distinct pathways in the central nervous system axis [8].…”
Section: Discussionmentioning
confidence: 99%